Sol-gel synthesis and particle size characterization of CdSe Quantum dots - Cuong, Khong Cat; Thien, Trinh Duc; Nga, Pham Thu; Minh, Nguyen Van; Hung, Nguyen Van (VNU Journal of Science: Mathematics - Physics, 2009)
Abstract